Blue Light: A Fascinating Journey (Nobel Lecture)1. Issue 27 (27th May 2015) - Akasaki, Isamu
<x xml:space="preserve">Abstract</x> In the beginning there was light: Mankind has pursued light sources since ancient times, starting with flames, then the development of electric light bulbs much later, and most recently the production of light‐emitting diodes. Isami Akasaki describes the historical progress that led to the invention of the first blue LED and related optical devices.